Information and analytical ensuring the acceptance of administrative decisions in the field of marketing - Valentyna Morokhova; Оlga Boiko; Оleg Kovalchuk (Економічний форум, 2023)
The article discusses the issue of information and analytical support for the development, support and implementation of marketing management solutions. It was established that the instability of the external environment of the functioning of enterprises requires them to make non-standard management decisions, intensify marketing efforts and individualize approaches to the needs of target consumers. Under these conditions, information and analytical support for marketing activities is an important tool for adapting enterprises to the unstable market situation. The study of the information and analytical component of the marketing activity of enterprises, which is used to observe, collect and analyze information about the internal and external environment, is summarized. It was emphasized that information and analytical support should not be reduced only to the accumulation of information resources. Its purpose should be to meet the needs of economic entities in the data complex, purposeful collection, processing, analysis and use of quality information, implementation of operational and strategic monitoring. Common tasks and differences between marketing analysis and marketing research are presented and discussed. Two main groups of marketing management decisions are distinguished: decisions in the field of strategic marketing and decisions in the field of tactical marketing. For the successful conduct of marketing activities and the adoption of effective management decisions, the need to use modern information technologies and modernize the marketing information system is substantiated. Research has proven that the effectiveness of marketing management decisions depends on the quality of information and analytical support for marketing activities. The insufficient level of information and analytical support leads to difficulties in the reliable assessment of the marketing potential of enterprises, which, in turn, becomes the reason for making unfounded decisions in the field of marketing. Ways to improve the information and analytical provision of the marketing component of the enterprise management system have been identified